Storytelling globalization from the Chaco and beyond - Blaser, Mario 1966- (New ecologies for the twenty-first century, 2010)
Laissez-faire progress : invisibilizing the Yrmo -- State-driven development : stabilizing modernity -- Sustainable development : modernity unravels? -- Enacting the Yrmo -- Taming differences -- Translating neoliberalism -- A world in which many worlds (are forced to) fit -- Becoming the Yshiro nation -- Reality check -- Eisheraho/renewal